The sentence is grammatically correct and free from error. Thus, E is the right answer.
Statements: Z > X > D > H ≤ M ≥ N = G
Conclusion
I: M > X
II: H > Z
Statements: P > O ≥ M ≤ N = W, X ≤ Z < Y < O
Conclusion:
I. P > X
II. O > X
III. Z ≤ N
Which of the following symbols should replace the sign (@) respectively in the given expression in order to make the expression P ≥ O and D > K defin...
Which of the following expressions will be true if the expression ‘V ≥ W < X = Y’ is definitely true?
Statements:
P < Q < R < S ≤ B < H; S > N ≥ Y
Conclusions:
I) P < Y
II) R ≥ N
Statements: A % I, I * Q, Q % R, R $ M
Conclusions :
I. M # I
II. M # Q
III. I # R
IV. Q % A ...
Statements:
A = C > E = F > D; Y < Z ≤ F
Conclusions:
I. E > Z
II. D ˃ Y
Which of the following expressions will be false if the expression V ≥ W > X = Y ≤ Z < A is definitely true?
Statements: P ≥ Q > S< T > R = U
Conclusions: I. P < S
II. U = S
Statements: A = C > G > H = B > O; E < P = R > B
Conclusions:
I). E > H
II). H ≤ E
...